2016
DOI: 10.1038/srep20166
|View full text |Cite
|
Sign up to set email alerts
|

Immunoglobulin G Expression in Human Sperm and Possible Functional Significance

Abstract: Immunoglobulin G (IgG), the major molecule of the immune system, which was traditionally thought to be produced by differentiated B-lymphocytes, had recently been found in non-immune cells including spermatozoa of rabbit testis. To study if human sperms could produce IgG that might play a role in fertilization, we employed immunofluorescent staining, Western blot, in situ hybridization, RT-PCR (reverse transcription polymerase chain reaction) and immunoelectron microscope and found that human sperms were capab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…Antibodies, also known as immunoglobulins (Igs), are expressed by B lymphocytes; however, accumulating evidence has indicated that Igs, including IgG, IgA and IgM, are produced in non-B lineage cells, such as epithelial cancer cells ( 6 – 9 ) and leukemic cells ( 10 12 ). Furthermore, several types of normal cells, including germ cells ( 13 , 14 ), neurons ( 15 , 16 ), endothelial cells ( 17 ) and skin epidermal cells ( 18 ), can also express Igs. Although non-B cell-derived Ig and traditional Ig have some similar characteristics, the former possesses unique characteristics, particularly with regards to structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies, also known as immunoglobulins (Igs), are expressed by B lymphocytes; however, accumulating evidence has indicated that Igs, including IgG, IgA and IgM, are produced in non-B lineage cells, such as epithelial cancer cells ( 6 – 9 ) and leukemic cells ( 10 12 ). Furthermore, several types of normal cells, including germ cells ( 13 , 14 ), neurons ( 15 , 16 ), endothelial cells ( 17 ) and skin epidermal cells ( 18 ), can also express Igs. Although non-B cell-derived Ig and traditional Ig have some similar characteristics, the former possesses unique characteristics, particularly with regards to structure and function.…”
Section: Introductionmentioning
confidence: 99%
“…Antibodies are normally synthesized by mature plasma cells. However, recent accumulating evidence suggests that non-lymphoid cells, such as human sperm ( 31 ), hepatocytes ( 32 ), certain carcinoma cells ( 25 , 32 , 33 ), and neurons from the central nervous system ( 34 37 ), also express genes required for antibody synthesis and produce antibodies. Here, we demonstrate that although DRG sensory neurons exhibit localization of antigen-specific antibodies, the neuronal cells do not express the essential enzymes required for generating antibody diversity.…”
Section: Discussionmentioning
confidence: 99%
“…IgG and RAG-1/RAG-2 expression was recently detected in human sperm, and an anti-IgG antibody was shown to inhibit sperm penetration of Zona-free hamster egg (Yan et al, 2016). Thus, sumoylation of RAG-1, which, to the best of our knowledge, has not previously reported, may be of importance in fertilization.…”
Section: Discussionmentioning
confidence: 99%
“…Beyond cytoskeleton regulation, RAG1, which is essential for IgG immunoglobulin synthesis and class switching, was another potentially important SUMO1 targets identified in this study. IgG and RAG-1/RAG-2 expression was recently detected in human sperm, and an anti-IgG antibody was shown to inhibit sperm penetration of Zona-free hamster egg (Yan et al, 2016 ). Thus, sumoylation of RAG-1, which, to the best of our knowledge, has not previously reported, may be of importance in fertilization.…”
Section: Discussionmentioning
confidence: 99%